A Critical Discourse Analysis of How Background Music Exhilarates Metal Gear Rising: Revengeance’s Narratives. - Putra, Rizky Anugrah (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2022)
Games have evolved beyond entertainment and become captivating spectacles with interesting stories and visuals. While most prioritize visuals, Metal Gear Rising: Revengeance is popular in 2022 due to its combination of music and story, making it a phenomenal meme. Because of this phenomenon, the researcher wants to examine how music can enhance the story elements of a game. To get an answer to this phenomenon, the researcher operates Fairclough's critical discourse analysis to examine the seven-song lyrics contained in the game Metal Gear Rising into three dimensions of analysis: microstructure, mesostructure and macrostructure. The researcher found that the song's lyrics enrich the narrative elements of the MGSR series by utilizing six styles of language: symbolism, metaphor, hyperbole, rhetoric, personification, and tautology. This research can provide an initial report on the association between literature, aesthetics and music in popular culture.